THE COMPETITIVE-COOPERATIVE TRIANGLES IN INTERNATIONAL RELATIONS: A THEORETICAL CONTRIBUTION OF POWER FROM THE CASE STUDY OF INTERNAL AND EXTERNAL POLITICAL FORCES IN SOUTH AMERICA - Rodrigues, Bernardo Salgado (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
In the 21st century, power projects in South America constitute disputes that comprise a dialectical correlation between Internal and External Political Forces. In this sense, this article aims to conduct an innovative debate based on the theoretical formulation called Competitive-Cooperative Triangles of Power, taking the South American region as a case study. From a realist view of international relations and by using an empirical-deductive methodology, the objective is to achieve an epistemological construction regarding power in the international system, explaining the challenges and possibilities of the South American Internal Political Forces.